2023
DOI: 10.1101/2023.02.03.526997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer relevance of circulating antibodies against LINE-1 antigens in humans

Abstract: LINE-1 (L1), the most abundant family of autonomous retrotransposons occupying over 17% of human DNA, is epigenetically silenced in normal tissues but frequently derepressed in cancer, suggesting that L1-encoded proteins may act as tumor-associated antigens recognized by the immune system. Here, we established an immunoassay for detecting circulating autoantibodies against L1 proteins in human blood. Using this assay in >3,000 individuals with or without cancer, we observed significantly higher IgG titers a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
(102 reference statements)
1
1
0
Order By: Relevance
“…However, we cannot be certain whether we are dealing with bone fide innate (i.e., genetically, and developmentally predetermined) or the observed phenomenon is a form of adaptive response, which is developed to spontaneous desilencing of L1 in rare cells with erroneously broken epigenetic control over expression of DNA repeats. Similar uncertainty exists about the origin of circulating antibodies to L1 antigens found in most healthy humans in our recent study 19 Regardless of its innate or adaptive nature, the observed phenomenon is likely to be an important contributor to a battery of natural cancer prevention mechanisms acting in mammals to eradicate cells with desilenced L1 occurring at early stages of transformation 34,42 . In addition to anticancer function, it may have an anti-aging immunosenolytic role clearing organism from senescent cells known to acquire expression of L1 43,44 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, we cannot be certain whether we are dealing with bone fide innate (i.e., genetically, and developmentally predetermined) or the observed phenomenon is a form of adaptive response, which is developed to spontaneous desilencing of L1 in rare cells with erroneously broken epigenetic control over expression of DNA repeats. Similar uncertainty exists about the origin of circulating antibodies to L1 antigens found in most healthy humans in our recent study 19 Regardless of its innate or adaptive nature, the observed phenomenon is likely to be an important contributor to a battery of natural cancer prevention mechanisms acting in mammals to eradicate cells with desilenced L1 occurring at early stages of transformation 34,42 . In addition to anticancer function, it may have an anti-aging immunosenolytic role clearing organism from senescent cells known to acquire expression of L1 43,44 .…”
Section: Discussionsupporting
confidence: 73%
“…Since these sites are all behind immunological barriers and, therefore, do not participate in the formation of immune tolerance to autoantigens, one would expect that L1 antigens expressed in tumors should be recognized by the immune system as tumor-associated antigens and induce an adaptive immune response. In fact, in our recent study we found a frequent association of the ongoing carcinogenic process in humans with several cancer types with elevated levels of anti-ORF1p -ORF2p antibodies in blood 19 . Here, we planned to test, using mouse models, whether one could utilize adaptive T-cell response to suppress growth of L1-expressing tumors.…”
Section: Introductionmentioning
confidence: 81%